2013
DOI: 10.1590/s0100-29452013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade e sazonalidade de crisomelídeos (Coleoptera: Chrysomelidae) em pomar, no município de Ponta Grossa, Paraná, Brasil

Abstract: RESUMO -Este trabalho teve como objetivo levantar informações sobre os padrões de composição faunística, estrutura da comunidade e sazonalidade de Chrysomelidae num pomar localizado na região dos Campos Gerais do Paraná. Durante cerca de dois anos de amostragem, foram coletados 3.661 coleópteros e, destes, 1.103 crisomelídeos, representando 30,1% dos besouros capturados. Eumolpinae e Galerucinae foram as duas subfamílias que apresentaram maior abundância e riqueza de espécies, sendo que as oito mais representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Basso et al (1974) also reported that this insect attacks the eggplant (Solanum melongela). Milléo et al (2013) mentioned that I. dives occur very often in various fruit tree orchards (orange, lemon, tangelo, tangerine, persimmon, apple, nectarine, pear, peach). Wiest and Barreto (2012), reporting the insect pests evolution on soybean crops in Mato Grosso state, mentioned that in 1988 I. dives was considered a secondary pest of this crop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basso et al (1974) also reported that this insect attacks the eggplant (Solanum melongela). Milléo et al (2013) mentioned that I. dives occur very often in various fruit tree orchards (orange, lemon, tangelo, tangerine, persimmon, apple, nectarine, pear, peach). Wiest and Barreto (2012), reporting the insect pests evolution on soybean crops in Mato Grosso state, mentioned that in 1988 I. dives was considered a secondary pest of this crop.…”
Section: Resultsmentioning
confidence: 99%
“…The Chrysomelidae family consists of various coleopterous, including the Iphimeis dives species (Germar, 1824), also known as vine defoliator beetle or green beetle, which has been reported attacking various fruit trees, some crops and vegetables (Basso et al, 1974;Mariconi, 1962;Milléo et al, 2013;. Wiest and Barreto, 2012).…”
Section: Introductionmentioning
confidence: 99%